Whole exome sequencing identifies two novel variants in PHEX and DMP1 in Malaysian children with hypophosphatemic rickets - Nahid Tavana; Tzer Hwu Ting; Kaitao Lai; Marina L. Kennerson; Karuppiah Thilakavathy (BMC, 2022)
Abstract Background Hypophosphatemic rickets (HR) is a genetic disease of phosphate wasting that is characterized by defective bone mineralization. The most common cause of the disease is mutations in the phosphate regulating gene with homologies to endopeptidases on the X chromosome (PHEX) gene. The aims of this study were to identify the gene variants responsible for HR in three cases of Malaysian origin from three independent families and to describe their clinical, biochemical, and radiological features. Methods Whole exome sequencing (WES) was performed on all patients and their parents, followed by Sanger sequencing validation. Bioinformatics tools were used to provide supporting evidence for pathogenicity of variants. To confirm that a mutation is de novo, paternity test was carried out. High resolution melting curve analysis was performed to assess the allele frequency in normal controls for mutations that were found in the patients. Results The patients showed typical characteristics of HR including lower limb deformity, hypophosphatemia, and elevated alkaline phosphatase. WES revealed two variants in the PHEX gene and one variant in the dentin matrix protein 1 (DMP1) gene. Two of the three variants were novel, including c.1946_1954del (p.Gly649_Arg651del) in PHEX and c.54 + 1G > A in DMP1. Our data suggests that the novel p.Gly649_Arg651del variant is likely pathogenic for HR disease. Conclusions This study extends the variant spectrum of the PHEX and DMP1 genes. Our findings indicate that WES is an advantageous approach for diagnosis of genetic diseases which are heterogeneous.